SCHEDULING OF N TASKSON M MACHINES WITH REACHING THE OBJECTIVE OF MINIMIZING MAKESPAN - OLGA-IOANA AMARIEI; CODRUȚA-OANA HAMAT (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
The present article has the purpose of establishing the launching order in production of n tasks, which are processed in a production cell, having different succesions of execution of operations on m machines, with reaching the main objective of minimizing makespan. It started from a case study in which we wanted to develop an own methodology of design of lower rank production systems, using several softwares, but because of it’s complexity, the study is truncated, being the subject of several specialized articles.